Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

10c - 6(2c - 1) = -2( c- 3) Your answer

Sagot :

10c - 6(2c - 1) = -2( c- 3)

[tex]10c-6\left(2c-1\right)=-2\left(c-3\right)[/tex]

in this case, we have a equation with an unknown value (c9

Step 1

operate to eliminate ()

[tex]\begin{gathered} 10c-(6\cdot2c)-(6)(-1)=-2c+6 \\ 10c-12c+6=-2c+6 \\ 10c-12c+2c=6-6 \\ 12c-12c=0 \\ 0=0 \end{gathered}[/tex]

it means, that for any value of x, it will work

this equation has infinite solutions